The New Frontiers in Neurodegenerative Diseases Treatment: Liposomal-Based Strategies - Cascione, Mariafrancesca; De Matteis, Valeria; Leporatti, Stefano; Rinaldi, Rosaria (Frontiers in Bioengineering and Biotechnology, 2020)
In the last decade, the onset of neurodegenerative (ND) diseases is strong widespread due to the age increase of world population. Despite the intensive investigations boosted by scientific community, an efficacious therapy it has not been outlined yet. The drugs commonly used are only able to relieve the symptom severity; following their administration orally or by intravenous route, their efficiency is strictly limited by the fact that just a small fraction is able to reach the Central Nervous System (CNS) overcoming the Blood Brain Barrier (BBB). Starting from these assumptions, the engineered-nanocarriers such as lipid-nanocarriers, are suitable agents to enhance the delivery of drugs into CNS due to their solubility, bioavailability and stability. Liposomal delivery systems are considered to be the ideal carriers, not only for conventional drug, but also for neuroprotective small molecules and green-extracted compounds. In the current work, the liposome-based drug delivery improvements in in vivo applications against ND disorders were reviewed.